Demographic Characteristics and Pattern of Acute Poisoning in Rangpur Medical College Hospital - Mondal, Ratindra Nath; Rani, Moni; Nurmohammad, -; Islam, Md. Monjurul; Haque, Md. Ashraful; Nasreen, Farida (Bangladesh Journal of Medicine, 2013)
Bangladesh Journal of Medicine, Vol 23 No 2, 2012, Page 62-66 DOI: http://dx.doi.org/10.3329/bjmed.v23i2.14986